Frequency & Predictors of Depression in Patients of Chronic Heart Failure with Reduced Ejection Fraction (HFrEF) (Bangladesh Heart Journal, 2024)
Background: Clinically significant depression is estimated to occur in a significant portion of chronic heart failure (CHF) patients and increases sharply with increase in heart failure severity. However, the frequency and predictors of depression in this group of patients are underreported. This study was designed to assess frequency & predictors of depression in patients of chronic heart failure with reduced ejection fraction (HFrEF).Methods: This cross-sectional analytical study was performed in the department of Cardiology, Dhaka Medical College Hospital, Dhaka, during the period from October’2018 to Septemeber’2019. One hundred and fifty-two CHF patients with reduced ejection fraction (